Discapacidad, diversidad e inclusión: concepciones de fonoaudiólogos que trabajan en educación inclusiva - Jhon Fredy Quintero-Uribe; Mary Luz Osorio-Montoya (Universidad de Antioquia, 2018)
Introduction: The work of health professionals, such as speech therapists, is permeated in the educational sphere by views or conceptions that can lead to practices of exclusion or inclusion. In Colombia, speech therapists have achieved a space in the education sector, and their role has become relevant in the nascent inclusive education approach. Objective: To know what conceptions some of the speech therapists who work in inclusive education have about what "disability", "diversity" and "inclusion" are, expressions that are related to their work. Methodology: A qualitative approach was applied with descriptive-transverse design. A semi-structured interview was carried out. For data analysis, open and axial coding was used to identify categories. Results: Some of the speech therapists interviewed showed conceptions about disability that are construed from the medical or rehabilitative model, and conceptions about diversity and inclusion in accordance with unesco's proposals for education for all. Conclusion: It is important to continue reflecting on the training of future speech therapists within the framework of the World Health Organization and unesco approaches and proposals.